The Effect of Networks on Organizational Missions. (June 2015) - Koch, Bradley J.; Galaskiewicz, Joseph; Pierson, Alisha
We examine the effects of nonprofit organizations' resource streams and network ties on changes to the services provided and clientele served as specified in the mission statements. The organizations' network ties are used to develop a measure of the services and beneficiaries mentioned in their inter-organizational (IO) peers' mission statements. These measures of the content of peers' mission statements were significant in predicting future changes in organizations' mission statements. We argue that although mission statements are consistent with the rational systems approach by directing action toward some goal, future mission activities and clientele are greatly influenced by nonprofits' IO ties, which is consistent with a hybrid open-natural systems approach.